Valores glicêmicos de ratas diabéticas e sua relação com os critérios diagnósticos estabelecidos para o diabetes mellitus gestacional, desfechos reprodutivos maternos e perinatais - Holtz, Beatriz Martins [UNESP] (UNESP, 2024)
Diabetes mellitus (DM) is a disease that generates chronic hyperglycemia and can result in secondary complications. Diagnostic criteria for diabetes are methods for detecting the illness and its clinical management. However, unlike the criteria established for non-pregnant diabetic women, there is no single consensus in the current scenario for the diagnosis of Gestational Diabetes mellitus (GDM) by regulatory agencies. Long-term studies in experimental models with rodents are often used in maternal and embryofetal evaluations. Therefore, it is important to highlight the best way to perform the selective diagnosis of diabetic rates using the OGTT (Oral Glucose Tolerance Test) as performed in pregnant women. For this purpose, two chapters were prepared to compose this Dissertation: Chapter 1: Due to the controversies among regulatory agencies for the screening and management of diabetes in pregnant women, there is no single consensus in the current scenario for the diagnosis of GDM. Therefore, a review of articles was carried out with the aim of listing the evolution of diagnostic criteria for GDM, focusing on the influence of large clinical trials on current standards and exploring areas where gaps and divergences between guidelines still exist. This is a bibliographic update on the diagnostic criteria for gestational diabetes mellitus in women and its evolution in recent decades. To cover the main definitions and approaches, studies published in the PubMed, Embase, Scopus and Scielo databases in Portuguese, Spanish and English were included. For Chapter 2: The study aims to relate the blood glucose levels found and stored in our database of female rats with moderate diabetes who underwent the oral glucose tolerance test (OGTT) in relation to the blood glucose levels obtained in the OGTT that are included in the database of clinical research of pregnant women with and without diabetes. The objective is to verify a specific time in the OGTT that is a prior identifier of complications resulting from hyperglycemia in pregnancy and related to the maternal reproductive outcomes of rats. Therefore, the clinical studies selected for descriptive analysis demonstrate that the IADPSG diagnosis, currently recommended by the ADA, is the most effective in the early identification of gestational diabetes mellitus (GDM) and works as a predictor of maternal-fetal risks. Regarding the following chapter, blood glucose levels around 180 mg/dL already consist of translational results, since the blood glucose levels of rats at time 30 of the OGTT are similar to those of women at time 60 of the OGTT. In addition, the maternal-fetal outcomes were compatible with those of diabetic pregnant women.

Diabetes mellitus (DM) é uma doença que gera hiperglicemia crônica e pode resultar em complicações secundárias. Os critérios diagnósticos para o diabete são métodos para a detecção da doença e seu manejo clínico. No entanto, diferente dos critérios estabelecidos para mulheres diabéticas não-grávidas, não há um consenso único no cenário atual para o diagnóstico do Diabetes mellitus Gestacional (DMG) pelas agências normativas. Estudos conduzidos em modelos experimentais com roedores são frequentemente utilizados em avaliações maternas e embriofetais. Desta forma, é importante destacar a melhor forma para realização do critério diagnóstico de ratas diabéticas utilizando o TOTG (Teste oral de tolerância à glicose) como feito nas gestantes. Para isso, foram elaborados dois capítulos para compor esta Dissertação: Capítulo 1: Pelo fato de haver controvérsias entre as agências normativas para o rastreio e manejo do diabete em gestantes, não há um consenso único no cenário atual para diagnóstico do DMG. Por isso, foi realizada uma revisão de artigos que teve como objetivo elencar a evolução dos critérios diagnósticos para DMG, com foco na influência de grandes ensaios clínicos nos padrões atuais e explorar as áreas onde ainda existem lacunas e divergências entre as diretrizes. Trata-se de uma atualização bibliográfica sobre os critérios diagnósticos do Diabete mellitus gestacional em mulheres e sua evolução nas últimas décadas. Para abranger as principais definições e abordagens, foram incluídos estudos publicados nas bases de dados PubMed, Embase, Scopus e Scielo nos idiomas português, espanhol e inglês. Para o Capítulo 2: O estudo visa relacionar as glicemias obtidas e armazenadas em nosso banco de dados de ratas com diabete moderado que foram submetidas ao teste oral de tolerância à glicose (TOTG) em relação às glicemias obtidas no TOTG que constam no banco de dados das pesquisas clínicas de gestantes com e sem diabete. O objetivo é verificar um tempo específico no TOTG que seja um identificador prévio das complicações decorrentes da hiperglicemia na gestação e relacionar com os desfechos reprodutivos maternos das ratas. Portanto, os estudos clínicos selecionados para análise descritiva demonstram que o critério diagnóstico do IADPSG, atualmente recomendado pela ADA, é o mais eficaz na identificação precoce do Diabetes mellitus gestacional (DMG) e funciona como um preditor de riscos maternofetais. Com relação ao capítulo seguinte, as glicemias em torno de 180 mg/dL já consistem em resultados translacionais, visto que a glicemia das ratas no tempo 30 do TOTG das ratas se equipara aos das mulheres no tempo 60 do TOTG. Além disso, os desfechos maternofetais foram compatíveis aos existentes nas gestantes diabéticas .
Glycemic values ​​of diabetic rats and their relationship with the diagnostic criteria established for gestational diabetes mellitus, maternal and perinatal reproductive outcomes
Keywords: estudos translacionais; gravidez; glicemia; diabete